Islamic Educational Values in Local Wisdom Traditional Tradition of Mappogau Sihanua Karampuang Sinjai District - Mustamin Mustamin; Syamsudduha Saleh; Abd. Rahim Razak; Ilham Muchtar; Suriyati Suriyati (IJORER : International Journal of Recent Educational Research, 2023)
Objective: this research is a preliminary study that aims to describe the process of implementing traditional ceremonial traditions and Islamic values and the impact of acculturation of Islamic education on Mappogau Sihanua Karampuang. Method: This study uses field research with a descriptive qualitative approach. Data collection techniques are observation, interviews, and documentation. The subjects in this study were ten community leaders directly involved in implementing the Karampuang traditional ceremony and two educators. Results: This study found that in the Mappogau Sihanua tradition, several ritual processes must be passed, namely: Mabbahanang is deliberation, Mappaota. It is a request for permission or blessing. Mabaja-baja is cooperation to clean houses and traditional locations, menre ri fur (going up to the top of a mountain to release vows), mabbali sumange, preparing traditional medicines, and Malling is a prohibition on slaughtering livestock. The most numerous messages of value in the Mappogau Sihanua Karampuang time-honored tradition are moral values such as respecting each other, preserving the environment, respecting leaders, cooperation/helping each other, ukhuwah, and friendship values. Novelty: The novelty in this study is that the values of Islamic religious education can have a positive impact and give the Karampuang community new perspectives on something new in behavior.